2017
DOI: 10.7717/peerj.3830
|View full text |Cite
|
Sign up to set email alerts
|

MazF activation promotes translational heterogeneity of thegrcAmRNA inEscherichia colipopulations

Abstract: Bacteria adapt to adverse environmental conditions by altering gene expression patterns. Recently, a novel stress adaptation mechanism has been described that allows Escherichia coli to alter gene expression at the post-transcriptional level. The key player in this regulatory pathway is the endoribonuclease MazF, the toxin component of the toxin-antitoxin module mazEF that is triggered by various stressful conditions. In general, MazF degrades the majority of transcripts by cleaving at ACA sites, which results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 56 publications
(114 reference statements)
1
16
0
Order By: Relevance
“…We furthermore observed that the extent of variation in mCherry fluorescence was dependent on the induction level of mazF expression; low l -arabinose concentrations (1 × 10 −7 %) caused neither growth arrest nor multimodal patterns of mCherry fluorescence ( Supplementary Figure S4 ). Similarly, induction with 0.1% Ara from a single-copy chromosomally encoded P BAD - mazF system ( Supplementary Figure S9 ) resulted in growth adaptation, a decrease in growth yield by 20% (similarly shown in ( 29 )), and unimodal distributions of mCherry fluorescence ( Supplementary Figure S10 ).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…We furthermore observed that the extent of variation in mCherry fluorescence was dependent on the induction level of mazF expression; low l -arabinose concentrations (1 × 10 −7 %) caused neither growth arrest nor multimodal patterns of mCherry fluorescence ( Supplementary Figure S4 ). Similarly, induction with 0.1% Ara from a single-copy chromosomally encoded P BAD - mazF system ( Supplementary Figure S9 ) resulted in growth adaptation, a decrease in growth yield by 20% (similarly shown in ( 29 )), and unimodal distributions of mCherry fluorescence ( Supplementary Figure S10 ).…”
Section: Resultsmentioning
confidence: 79%
“…It is conceivable that the extent of MazF activation upon physiological stress resembles mild ectopic mazF expression in laboratory setups ( 19 , 56 ). Even though stressed populations activate MazF at low levels ( 29 , 57 ), the MazF-mediated pathway might be an important strategy for cells to respond to stress rapidly and efficiently, and to optimize growth resumption after the stressor is gone. When bacterial cells encounter long-term adverse conditions in environment or in host, the subtle MazF-mediated response might be complemented by the activation of other TA systems ( 26 , 41 , 42 ) or stress response mechanisms ( 58 , 59 ) that allow for complex regulation of gene expression and growth, and eventually result in persistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another case, the existence of mazF-induced specialized ribosomes in bacteria has recently been questioned (Culviner and Laub 2018). Previous work, relying on reporter assays and assaying only the "specialized" ribosome populations, appeared to show that under stress sitespecific cleavage by mazF generates a pool of leaderless mRNAs that are preferentially translated by ribosomes cleaved by the same nuclease (Vesper et al 2011;Sauert et al 2016;Nikolic et al 2017). However, a recent genome-wide analysis of this system shows that these ribosomes and mRNAs are instead the product of widespread mRNA and rRNA cleavages, and thus possibly degradation intermediates, and failures of ribosome biogenesis (Culviner and Laub 2018).…”
Section: The Expression Of Ribosomal Protein Paralogs Is Differentialmentioning
confidence: 99%
“…Conditional cooperativity has also been suggested for the autoregulation of mazEF expression (Zorzini et al 2015 ). During exponential growth, the expression of the mazEF module is strongly repressed (Marianovsky et al 2001 ; Nikolic et al 2017 ). Analysis of the mazEF promoter activity in a mazF deletion strain, when the toxin to antitoxin ratio is artificially shifted in favor of the MazE antitoxin, shows weak repression of the mazEF operon.…”
Section: Transcriptional Autoregulation Of Ta Systemsmentioning
confidence: 99%